Ecological and Landscape Perspectives on Urban Forest Planning and Construction: A Case Study in Guangdong-HongKong-Macao Greater Bay Area of China - Zhao, Qing; Xu, Dongxian; Qian, Wanhui; Hu, Rouxuan; Chen, Xingcheng; Tang, Honghui; Zhang, Chi (Frontiers in Sustainable Cities, 2020)
Urban forest plays a crucial role in coping with global change and rapid urbanization, such as improving air quality, fixing carbon, mitigating environmental degradation, and providing other ecosystem services. In this context, cities in Guangdong-Hongkong-Macao Greater Bay Area of China (GBA) established increasing investment in urban forest construction since 2000. However, data on the current condition of the planted forests remains scarce, which hampers a comprehensive understanding of how to improve the quality of urban forest planning and construction in the future. Therefore, we selected a core city Guangzhou, an inland city Foshan and a coastal city Zhuhai in GBA as our research objects and launched a field measurement for the forest structure. Besides, ecological and landscape indexes were introduced to evaluate the potential, diversity, and stability of the forests in the core urban area (CUA), semi urban area (SUA), and urban fringe area (UFA) of the three cities. The results show that Guangzhou has a well-planned forest pattern with advantages in forest structures and visible landscape values in different areas. To introduce different tree species in CUA and SUA and to plant more trees of those rare tree species in UFA can effectively increase Guangzhou’s forest diversity and evenness. For Foshan, it is advisable to implement a balanced forest-investment policy by making specific recommendations for different areas, such as planting various tree species in CUA and UFA to increase forest diversity. Zhuhai is distinguished for the attractiveness for tourists by the advantages in landscape diversity and stability, but it is still necessary to plant different trees with appropriate classes to enhance the urban forest stability. Overall, it is crucial for city managers to obtain precise knowledge of urban forest conditions from both the ecological and landscape perspectives, which may contribute enormously to the improvement of the quality of urban forest planning and construction in adapting to various environmental challenges.